Targeting thyroid hormone receptor-β agonists to the liver reduces cholesterol and triglycerides and improves the therapeutic index - Erion, Mark D; Cable, Edward E; Ito, Bruce R; Jiang, Hongjian; Fujitaki, James M; Finn, Patricia D; Zhang, Bao-Hong; Hou, Jinzhao; Boyer, Serge H; van Poelje, Paul D; Linemeyer, David L (Proceedings of the National Academy of Sciences - PNAS, 2007)
Despite efforts spanning four decades, the therapeutic potential of thyroid hormone receptor (TR) agonists as lipid-lowering and anti-obesity agents remains largely unexplored in humans because of dose-limiting cardiac effects and effects on the thyroid hormone axis (THA), muscle metabolism, and bone turnover. TR agonists selective for the TRβ isoform exhibit modest cardiac sparing in rodents and primates but are unable to lower lipids without inducing TRβ-mediated suppression of the THA. Herein, we describe a cytochrome P450-activated prodrug of a phosphonate-containing TR agonist that exhibits increased TR activation in the liver relative to extrahepatic tissues and an improved therapeutic index. Pharmacokinetic studies in rats demonstrated that the prodrug (2R,4S)-4-(3-chlorophenyl)-2-[(3,5-dimethyl-4-(4'-hydroxy-3'-isopropylbenzyl)phenoxy)methyl]-2-oxido-[1,3,2]-dioxaphosphonane (MB07811) undergoes first-pass hepatic extraction and that cleavage of the prodrug generates the negatively charged TR agonist (3,5-dimethyl-4-(4'-hydroxy-3'-isopropylbenzyl)phenoxy)methylphosphonic acid (MB07344), which distributes poorly into most tissues and is rapidly eliminated in the bile. Enhanced liver targeting was further demonstrated by comparing the effects of MB07811 with 3,5,3'-triiodo-L-thyronine (T₃) and a non-liver-targeted TR agonist, 3,5-dichloro-4-(4-hydroxy-3-isopropylphenoxy)phenylacetic acid (KB-141) on the expression of TR agonist-responsive genes in the liver and six extrahepatic tissues. The pharmacologic effects of liver targeting were evident in the normal rat, where MB07811 exhibited increased cardiac sparing, and in the diet-induced obese mouse, where, unlike KB-141, MB07811 reduced cholesterol and both serum and hepatic triglycerides at doses devoid of effects on body weight, glycemia, and the THA. These results indicate that targeting TR agonists to the liver has the potential to lower both cholesterol and triglyceride levels with an acceptable safety profile.